Seemingly irrelevant factors and willingness to block polluting investments - Nicolas Ajzenman; Lenin H. Balza; Hernan Bejarano; Camilo de los Rios Rueda; Nicolas Gomez-Parra (Inter-American Development Bank (IDB), 2023)
Using an online multi-country video-vignette survey experiment, we measure bias against extractive industries and foreign firms in individuals perceptions and preferences related to industrial projects with potential economic benefits and environmental costs. Individuals face a hypothetical industrial investment project with a randomly assigned implementing firm, which varies in one or two dimensions: nationality (foreign or national), and industrial sector (extractive or generic). We elicit several incentivized and non-incentivized measures of acceptance of hypothetical investments. We find a precisely estimated null effect on willingness to pay to block the projects across experimental treatments: respondents express similar reactions to the same information independently of the firms origin or industrial sector.
Keywords: C90; D70; D90; L71; Q30; Q51; 330; experimental economics; extractive industries; perceptions; willingness-to-pay; valuation